Students Conceptual Understanding of Energy: Classroom Action Research with Contextual Learning - Asnaini (Universal Education Jurnal Teaching and Learning, 2024)
This study aims to improve students' ability to understand the concept of Energy. This research is a classroom action research conducted in two cycles. The action is implemented by applying contextual learning. The research was conducted at SDN 144/V Betara Kiri with 29 students. The types of data in this study are quantitative data and qualitative data. Quantitative data were obtained from tests at the end of each lesson in each cycle, and qualitative data were obtained from observations in the implementation of actions. Quantitative data analysis was carried out by determining the average score of students' understanding of the concept of effort and energy. Qualitative data were analyzed with the aim of improving the implementation of the action. The learning results show that students' ability to understand the concept of Energy has increased with the application of contextual learning. This is indicated by the increased ability to understand concepts from 68.22 in cycle I to 81.63 in cycle II.